Improvement of Coconut Production in Kenyan Coast for Income Generation - Oyoo, Maurice (Academia Kenya, 2021)
The potential value of the coconut sub-sector is estimated at US$180.6 million. But the actual value is only 25 percent of that (US$44.5 million) annually and consists of nuts (mature and immature-madafu) accounting for about 24 percent, coconut wine (60 percent), Makuti roofing materials (12 percent), brooms (3.3 percent) and coconut wood (1 percent). The low level of productivity is due to old and unproductive orchards – the East African Talls (EAT) with no designed improvement programme since they were introduced in Kenya, inadequate quality planting material, lack of fast means of generating clean planting materials, unavailability of improved varieties and a general lack of value addition (Muhammed et al., 2013). Slow growth and long pre-breeding period of palm is also a factor (Rajesh et al., 2008).
Keywords: Agriculture; Coconut; Kenya